CODE MIXING IN NOVEL TAKBIR CINTA ZAHRANA - Titi Dewi Rohati; Dadan Hidayat (LPPM Universitas Bina Sarana Informatika, 2019)
In using language, there are a lot of varieties in represent the language. One of them is code mixing. Indonesian people use code mixing not only in speaking but also in written text. One of written text contains code mixing is novel Takbir Cinta Zahrana. In the novel, the authot represent the characters use code mixing in their daily conversation. They mixes Bahasa and Javanese language. This paper is conducted to get some information about code mixing, especially in novel Takbir Cinta Zahrana The first one is about the level of code mixing, the second one is about factor of code mixing, and the last one is about reason why the characters in the novel using code mixing. The research used qualitative research. The data were collected from the contain of the novel. After doing analyzing, the researcher roll out some facts. The level of code mixing in the novel is dominated by word level, factors of using code mixing are popular term, speaker and speaker character, prestigious factor, and domicile and time of conversation. The last fact is 3 reasons of using code mixng in novel Takbir Cinta Zahrana. They are social roles and relationships of participants; situational factors: discourse topic and language allocation; message-intrinsic considerations; and language attitudes including social dominance and security.